Crater catalog and analysis of crater distribution on Saturn's moon, Enceladus. - Karpes, Brian Allan. (Northern Illinois University.Geology and Environmental Geosciences., 2009)
Sorry, the full text of this article is not available in Huskie Commons. Please click on the alternative location to access it. 110 p. This project consists of a catalog of all craters greater than 2.2 km (0.5°) in diameter, and categorizing them in terms of deformations limited to rifting and/or elongation. Publicly available images were obtained from the Cassini Imaging website, and loaded into Adobe Photoshop(TM) to derive the location and size of the craters.The distribution of craters was then analyzed by latitude and longitude. The enigmatic distribution of craters is explained by the possibilities that Saturn acts as a planetary shield for the sub-Saturn hemisphere and that the E-ring is weathering and eroding craters on the leading hemisphere. Furthermore, the lack of craters in the trailing hemisphere supports a hypothesis that a south-pole-style hot spot once existed in the eastern hemisphere equatorial region.